2014
DOI: 10.4028/www.scientific.net/amm.567.631
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Orientations on the Room's Thermal Performance in the Tropics

Abstract: Thermal performance of terrace house in Malaysia very much depends on the spatial design due to limited responsive environment factors. Building orientation is one of the important responsive factors under design consideration. The main concerns of the opening’s orientation are solar radiation and wind. In Malaysia, the maximum amount of solar radiation directly affects the thermal performance and thus the orientation of the window should be designed in the way to minimize solar gain and maximize natural venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…East-West facing is the critical orientation for Singapore as it is located near the Equator, where the solar path does not change much throught out the year [6]. This similarity can be found in other studies conducted near the equator region such as Malaysia and Indonesia [24][25][26][27][28][29][30][31][32][33]. These researchers suggested that the East-West orientation for buildings near the equator region should be avoided.…”
Section: Building Orientationsupporting
confidence: 60%
“…East-West facing is the critical orientation for Singapore as it is located near the Equator, where the solar path does not change much throught out the year [6]. This similarity can be found in other studies conducted near the equator region such as Malaysia and Indonesia [24][25][26][27][28][29][30][31][32][33]. These researchers suggested that the East-West orientation for buildings near the equator region should be avoided.…”
Section: Building Orientationsupporting
confidence: 60%
“…In Malaysia, approximately 50 to 60% of electricity is consumed by air conditioning and mechanical ventilation per year especially in residential buildings [3]. In urban area such as Kuala Lumpur, residential housings take up the highest percentage of built-up land [4].…”
Section: Introductionmentioning
confidence: 99%
“…In regard to which the terraced housing is the most preferred dwelling type like in Johor Bahru where, 69.9% of the population preferred such land-dwellings [5]. Even so, through many statistical, field and simulation studies [3,[6][7][8] the occupants of such houses show high discomfort level which leads to the excessive use of air conditioning. In line with the Tenth Malaysian Plan [9] the use of electricity can be further reduced through the reintroduction of natural ventilation.…”
Section: Introductionmentioning
confidence: 99%